PSIV-37 Development of a genomic selection strategy to include meat quality traits in turkeys (Meleagris gallopavo). (7th December 2018) - Vanderhout, R; Wood, B; Barbut, S; Baes, C
Abstract: Genetic improvement of meat quality traits is challenging, as the phenotype is measured on an animal that can no longer be a selection candidate. Information from relatives, such as siblings, must therefore be used to estimate the breeding value of selection candidates. The objective of this research is to adapt meat quality traits developed in other livestock species, such as chicken and pigs, and apply them to a genomic selection program in turkeys. The project will consist of three main activities. The first activity consists of identifying meat quality traits, such as the rate of pH decline, ultimate pH, colour, and shear force. Body conformation will also be measured. Once identified and clearly defined, important traits will be measured on a large number of turkeys in the processing plant and the laboratory. In the second activity, genetic parameters will be estimated for the collected traits. Genetic correlations between the identified traits and other economically important traits, such as body weight and feed efficiency, will be estimated. In the final activity, genome-wide association studies and functional analyses will be performed using information from a 65K SNP array. In total, approximately 3, 000 birds will be phenotyped for meat quality traits, providing a reference population for SNP effect estimation. By defining relevant meat quality traits, estimating their genetic variances and correlations to production traits, and identifying genomic regions associated with these traits, the groundwork for implementing genomic selection for meat quality will be laid.